From macro growth to disaggragated production studies - Finn R. Førsund; Jon Vislie (University of Oslo, Department of Economics, 2011)
Professor Leif Johansen (1930 - 1982) made significant contributions to a large number of fields in economics. A short survey of his contributions is presented. The main focus in the paper is on his growth - production program constituting an important part of his research. The key concepts are embodied technical change, irreversibility, sunk cost, rigidities and heterogeneity. The impact of these factors on the nature of economic growth at the macro level is the point of departure of gradually disaggragating the level of analysis right down to the individual firm. An important tool for the analysis for dynamic structural change at the industry level is the short-run function capturing the underlying heterogeneity of the technologies of the firms within an industry. Technical rigidities represent constraints on how an economy develops from the level of a single industry up to the aggregated macro level of an economy.
Keywords: C61; D24; D92; E22; E23; 330; Dynamic structural change; Heterogeneity; Macroeconomic growth; Short-run industry production function; Technical rigidities; Vintage; Wachstumstheorie; Produktionstheorie; Dogmengeschichte; Norwegen